2015
DOI: 10.18632/oncotarget.3324
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and up-regulation ofPD-1in T cells by azacytidine in MDS/AML patients: A rationale for combined targeting of PD-1 and DNA methylation

Abstract: The hypomethylating agents (HMAs) are standard therapy for patients with higher-risk myelodysplastic syndrome (MDS); however, the majority of the patients will lose their response to HMAs over time due to unknown mechanisms. It has recently been shown that T cell expression of the immunoinhibitory receptor PD-1 is regulated by DNA methylation. In 12 of 27 patients (44%) PD-1 promoter demethylation was observed in sorted peripheral blood T cells isolated over consecutive cycles of treatment with 5-azacytidine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 39 publications
6
113
2
2
Order By: Relevance
“…This was supported by another study demonstrating that azacitidine-mediated PD-1 promoter demethylation was associated with PD-1 mRNA upregulation and worse overall response in MDS patients. These findings suggest that PD-1 promoter demethylation correlates with poorer clinical response to azacitidine [44]. It has been shown that, during infection, the expression of PD-1 on T cells is regulated by DNA methylation [122].…”
Section: Dnmti and Immune Checkpoint Inhibitorsmentioning
confidence: 94%
See 1 more Smart Citation
“…This was supported by another study demonstrating that azacitidine-mediated PD-1 promoter demethylation was associated with PD-1 mRNA upregulation and worse overall response in MDS patients. These findings suggest that PD-1 promoter demethylation correlates with poorer clinical response to azacitidine [44]. It has been shown that, during infection, the expression of PD-1 on T cells is regulated by DNA methylation [122].…”
Section: Dnmti and Immune Checkpoint Inhibitorsmentioning
confidence: 94%
“…Their application in cancer is limited by their modest clinical activity and relative toxicity [42] as single agents. Moreover, a majority of patients that benefit from HMAs will develop resistance due to unknown mechanism(s) [43,44]. Azacitidine is approved by the FDA for the treatment of myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia, and by the EMA for the treatment of acute myeloid leukemia (AML).…”
Section: Hdac and Hdacimentioning
confidence: 99%
“…Ørskov et al identified a correlation between PD-1 promoter demethylation and increased PD-1 expression in PB T-cells of patients with MDS, following consecutive cycles of AZA, that resulted into significantly worse ORR (8% vs. 60%, p = 0.014), and shorter OS (p = 0.11). A significantly higher baseline methylation level of the PD-1 promoter was observed in T-cells of non-responding patients also when compared to healthy controls (p = 0.023) 23. The HMT/ICI combination may increase treatment response due to demethylation and re-activation of genes related to interferon signaling, antigen presentation and inflammation, which may favour the activity of ICI 24…”
Section: Treatment Combinationsmentioning
confidence: 99%
“…There are early preliminary signals from in-vitro and in-vivo systems suggesting that a combination of HMA and PD1-blocking agents may have a pathophysiological rationale in AML and MDS (51,52). Clinical trials investigating such approaches have just started in the non-transplant setting and, if successful, might be expanded to the field of relapse after allo-SCT.…”
Section: Potential Combination Partnersmentioning
confidence: 99%